Efeito da adsorção e filtração na produção de celulases e xilanases - Ritter, Carla Eliana Todero (My University, 2015)
Cellulases and xylanases enzymes complex production stands out in the world because these enzymes are important for the generation of biofuels, resins, alcohols, xylitol, sorbitol, and for the detergents industry, animal feed, pulp bleaching, and in the extraction of oils, pigments and essences from lignocellulose biomass. Secretion and production of cellulases and xylanases are affected under catabolic repression conditions due to glucose release. The purpose of the present study was to verify the effect on enzymatic production of Penicillium echinulatum compared to metabolites and sugars during submerged cultivation. The strategies used for the substances removal from the medium included filtration application, the use of pellets with adsorbents, and the use of adsorbents films. Membranes preparation from both ceramic and polymeric supports impregnated with polymers PVDF and PA were performed by phase inversion method, and eventually the ceramic membrane impregnated with solution 10% (w/v) of PVDF (C1) held 88% of the total proteins from the enzymatic solution. The removal consisting in 10% or 20% from the permeate during filtration with flat membranes, in periods between 8h and 24h resulted in a rise in the activity regarding β-glucosidase and endoglucanase in Erlenmeyer flasks. In relation to xylanases activity, the titles observed on the fourth day were between 40% and 30% superiors when filtration was made in 42 and 44h, respectively. Subsequently, when adsorbents were used in the bioreactor, activity involving endoglucanase, CBH and xylonase increased 50%, 43% and 12% respectively, in concentration applying activated charcoal comparable to standard source. Moreover, tests performed with nanofiltration membranes allowed 95% retention of the enzymes from the complex, and when they were used in the removal consisted of 10% and 20% in liquid phase in flasks, results showed a rise on the enzymatic activity. The tests 18/20, 24/10, 24/20, 44/10 and 44/20 ( in relation to filtration day and volume permeated) presented, on average, in 72 hours, a 33% increment in the endoglucanase activity and, in 96 hours, the test 44/20 presented activity superior to 40% from standard value. Therefore, for tests with Trichoderma reesei Rut C30, filtration experiments with 10% of the volume of the flasks in 12h and 20 h presented an increase in FPA activity, and in 60 h, the amount found was 15% and 11%, respectively. Subsequently, for endoglucanase enzyme, the activity presented increment levels evaluated in 40,7% and 52, 2% respectively for the mentioned tests, demonstrating the positive factor of the permeate 10% removal from the enzymatic production. Lastly, for FPA the rise represented 15% and 11% in the same test conditions.
A produção de enzimas do complexo celulases e de xilanases se destaca no cenário mundial, pois estas são importantes para a geração de biocombustíveis, resinas, álcoois, xilitol, sorbitol, e para a indústria de detergentes e ração animal e processos de biobranqueamento, extração de óleos, pigmentos e essências a partir de biomassa lignocelulósica. A secreção e produção destas enzimas são afetadas pela repressão catabólica, devido à presença da glicose liberada. O objetivo do presente estudo foi verificar o efeito sobre a produção enzimática de Penicillium echinulatum de metabólitos e açúcares durante o cultivo submerso. As estratégias utilizadas para a remoção de substâncias do meio de cultivo incluíram filtração e uso de pellets com adsorventes e uso de filmes adsorventes. O preparo de membranas de suporte cerâmico e polimérico, impregnadas com os polímeros poli(fluoreto de vinilideno) (PVDF) e poliamida (PA), foi realizado por inversão de fases, sendo que a membrana cerâmica impregnada com solução 10% (m/v) de PVDF (C1) reteve 88% da proteínas totais da solução enzimática. A remoção de 10 ou 20% do permeado durante a filtração com membranas planas, em períodos de tempo entre 8h e 24h, resultou em aumento da atividade de β- glicosidase e endoglicanase em frascos Erlenmeyer. Com relação à atividade de xilanases, os títulos observados no 4º dia foram entre 40% e 30% superiores quando houve a filtração em 42 e 44 h, respectivamente. Quando adsorventes foram utilizados em biorreator, a atividade de endoglicanase, CBH e xilanase apresentaram um aumento de 50%, 43% e 12%, respectivamente, em meio concentrado utilizando carvão ativado quando comparado ao padrão. Os ensaios com membranas de nanofiltração permitiram retenção de 95% das enzimas do complexo e, quando utilizadas na remoção de 10% e 20% da fase líquida em frascos, resultaram em aumento na atividade enzimática. Os ensaios 18/20, 24/10, 24/20, 44/10 e 44/20 (tempo de processo, em horas, em que foi feita a filtração / volume percentual de permeado removido) apresentaram, em média, em 72 h, um incremento de 33% na atividade de endoglicanase, enquanto o ensaio 44/20, em 96h, apresentou atividade superior a 40% do padrão. Para os cultivos com Trichoderma reesei Rut C30, os ensaios com filtração de 10 % do volume dos frascos, em 12 h e 20 h apresentaram aumento da atividade de FPA, em 60 h de cultivo, de 15% e 11%, respectivamente. Nos mesmos ensaios, a atividade de endoglicanase apresentou incremento de 40,7% e 52,2%, respectivamente, demonstrando o efeito positivo da remoção de 10% de permeado sobre a produção enzimática. Já para FPA, o aumento representou 15% e 11 % para as mesmas condições
Keywords: Enzimas; Celulase; Xilanases; Penicillium; Enzymes; Cellulase; Xylanases; Penicillium